HiL Platform for Synchronous Reference Frame Impedance Measurement and Stability Assessment of Three-Phase Power Electronics Systems - Peng Q.; Yang J.; Guenter S.; Buticchi G.; Tan N.M.L.; Wheeler P. (Institute of Electrical and Electronics Engineers Inc., 2024)
As the penetration rate of renewable generation has risen in the last decades, power electronics converters are becoming more and more dominant in modern electrical power systems. Three-phase grid-connected converters provide an interface between the utility grid and distributed power sources such as photovoltaic (PV), wind turbines, energy storage systems, etc. Synchronization of these converters are always achieved through Synchronous Reference Frame (SRF). Thus, impedance-based stability analysis under SRF becomes a powerful tool to assess the system stability and optimize the converter design. However, precise measurement of the system impedance can be a difficult task in practice, particularly for high-capacity converters. In this paper, a hardware-in-the-loop (HiL) platform is proposed for measurement of the SRF impedance. Consequently, the impedance of an Active Front End (AFE) converter is measured and compared with the analytical small-signal model. The results show that measurement with the proposed HiL setup provides a powerful and accurate solution for impedance measurement that precludes the need for complete hardware testing. 2023 The Korean Institute of Power Electronics.